The Diagnostic Role of Hyperbilirubinemia in Complicated and Non -complicated Appendicitis - Zejnullahu, Valon; Isjanovska, Rozalinda; Bicaj, Besnik; Zejnullahu, Vjosa A.; Hamza, Astrit R.; Ivanova, Viktoria Caloska (Albanian journal of trauma and emergency surgery (Online), 2018)
Background: Acute appendicitis is one of the most frequent causes of abdominal pain. Early diagnosis is the key to success for the surgeon, followed by the treatment with operation or conservative treatment as a new approach, before the stage of gangrenous appendicitis or perforation occurs.Aim: This study aims to establish he role of hyperbilirubinemia as a laboratory marker in prediction of acute appendicitis in the early diagnosis.Materials and methods: This is a cross-sectional study; it included 201 patients admitted in the emergency ward with suspicion for acute appendicitis. All patients that participated in this study have been subject to appendectomy. The blood samples were taken from all patients in order to analyze the level of total/direct bilirubin.Results: The study samples of 201 patients consisted of 67.7% with complicated appendicitis and 32.3% with non-complicated appendicitis. The sensitivity, specificity, PPV, NPV for laboratory marker, as predictor for complicated vs non-complicated cases of appendicitis was as follows: Total bilirubin; specificity (72.3%), sensitivity (54.4%), PPV (80.4%), NPV (43.1%),Conclusion: Elevation of total/direct bilirubin level in patients with clinical signs of acute appendicitis might predict the stage of acute appendicitis, such prediction may help surgeons to provide accurate treatment of the disease without delay in the diagnosis. This accuracy can be further supplemented by using Alvarado scoring model during the clinical approach.